Assessing Farmers\' Willingness to Participation in Land Consolidation Projects in Meymeh District, Isfahan - Alireza yousefi; mahdiyeh shahabinejad; Amimozafar mini (تحقیقات کاربردی علوم جغرافیایی)
Agricultural sector has an important role in development of countries. One of the obstacles to development in this sector, especially in Iran is significant fragmentation of agricultural lands. The aim of this study is to assess the farmers’ willingness to participate in land consolidation project using structural equation modeling. The population of this study consists of all farmers of Meymeh County and its surrounding cities and villages and Niloofar-Abi cooperative of Vazvan city. Data were collected on a sample of 156 farmers through face-to-face interviews based on a comprehensive structured questionnaire. Before the survey, the reliability and validity of questionnaire was initially evaluated on a pre-test study respectively by using Cronbach’s alpha coefficient, expert’s judgment and Kaiser-Meyer-Olkin (KMO) criteria. The results of this study show that the most important factors on farmers' willingness to participation are crop acreage and number of plots which respectively has the greatest positive and negative effect. The awareness of the farmers about benefit of consolidation project is another factor which has significant and positive impact on farmers' willingness. Furthermore, level of farmers schooling has no significant effect.